Hot Interstellar Matter in Elliptical Galaxies - Kim, Dong-Woo.; Pellegrini, Silvia; SpringerLink (Online service) (New York, NY : Springer New York, 2012)
Based on a number of new discoveries resulting from 10 years of Chandra and XMM-Newton observations and corresponding theoretical works, this is the first book to address significant progress in the research of the Hot Interstellar Matter in Elliptical Galaxies. A fundamental understanding of the physical properties of the hot ISM in elliptical galaxies is critical, because they are directly related to the formation and evolution of elliptical galaxies via star formation episodes, environmental effects such as stripping, infall, and mergers, and the growth of super-massive black holes. Thanks to the outstanding spatial resolution of Chandra and the large collecting area of XMM-Newton, various fine structures of the hot gas have been imaged in detail and key physical quantities have been accurately measured, allowing theoretical interpretations/predictions to be compared and tested against observational results. This book will bring all readers up-to-date on this essential field of research.
Chapter 1. The Hot ISM of Elliptical Galaxies - A Brief History -- Chapter 2. Hot Gas Flows on Global and Nuclear Galactic Scales -- Chapter 3. Feedback and Environmental Effects in Elliptical Galaxies -- Chapter 4. AGN Feedback in Elliptical Galaxies: Numerical Simulations -- Chapter 5. Metal Abundances in the Hot ISM of Elliptical Galaxies -- Chapter 6. Abundances and Abundance Ratios in Stars and Hot Gas in Elliptical Galaxies -- Chapter 7. Hot Gas Morphology, Thermal Structure, and the AGN Connection in Normal Elliptical Galaxies -- Chapter 8. Dark Matter in Elliptical Galaxies.
Keywords: Physics; Astronomy; Physics; Astronomy, Astrophysics and Cosmology